PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR TEMATIK PESERTA DIDIK KELAS IV B SD NEGERI 1 PINANG JAYA - Putri, Dewi Nuryanti (Jurnal Analisis Pendidikan Sosial, 2024)
Problem in this research is SD Negeri 1 Pinang Jaya low result of thematic learning. Purpose of the research is to increase the result of thematic learning of student class 4B by using problem based learning model. Research type used in this research is class action research with every cycle consist of : planning, actuating, observing and reflection. Data collected in this research using observation sheet and formatif test questionnaire. Data collection Technique use in this research is non test and test technique. Data analytic technique using qualitative and quantitative. Result of this research show that problem based learning could improve study result of the students. Percentage of affective learning cycle 1 get good enough category, and in cycle 2 become better, and on cycle 3 get good result. Completeness of affective stidy result cycle 1 get good enough, cycle 2 good enough, cycle 3 excellent. Student psikomotor study result cycle 1 get skilled enough, cycle 2 skilled enough, cycle 3 very skilled. Average result of kognitif study cycle 1 show high enough result, cycle 2 high enough and very high on cycle 3.